Weight gain in the first week of life predicts overweight at 2 years: A prospective cohort study. Issue 1 (21st June 2017) - Feldman‐Winter, Lori; Burnham, Laura; Grossman, Xena; Matlak, Stephanie; Chen, Ning; Merewood, Anne
Abstract: In formula‐fed infants, rapid weight gain during the first week of life is associated with later obesity. To examine the association between weight gain during the first week and overweight at age 2 among infants with various feeding practices and the relationship between exclusive breastfeeding in early infancy and overweight, we enrolled a prospective cohort of healthy mother–infant dyads and followed them for 2 years. We enrolled 450 mother/infant pairs and obtained information on 306 infants at year 2. Weight change during the first week of life and detailed feeding information were collected during the first month of life. Anthropometric measures were collected at 2 years. Overweight was defined as body mass index (BMI) ≥85th percentile for age. At 2 years, 81% had normal weights and 19% were overweight. Maternal pre‐pregnancy BMI; infant birth weight; maternal education; and Women, Infants, and Children status were associated with the risk of overweight at age 2. Children who gained more than 100 g during the first week were 2.3 times as likely after adjustment ( p = .02) to be overweight at age 2 compared to infants who lost weight. There was no association between feeding type and BMI, but feeding type was significantly associated with change in weight at week 1 and anthropometric measurements at age 2. Infant weight gain in the first week of life is related to overweight at age 2, and exclusively breastfed infants are least likely to gain ≥100 g.